SIMPLE DERIVATIVE ECONOMIC TERMS (TAMADDUN NURI JURNALI, 2025)
This article analyzes the role and importance of simple derivative economic terms within the system of economic terminology. Such terms, formed at the intersection of linguistics and economics, help convey economic concepts clearly and concisely. The article provides examples of Uzbek simple derivative economic terms and their equivalents in Russian and English.